2005
DOI: 10.1063/1.1924543
|View full text |Cite
|
Sign up to set email alerts
|

Classical trajectory study of collisions of Ar with alkanethiolate self-assembled monolayers: Potential-energy surface effects on dynamics

Abstract: We have investigated collisions between Ar and alkanethiolate self-assembled monolayers (SAMs) using classical trajectory calculations with several potential-energy surfaces. The legitimacy of the potential-energy surfaces is established through comparison with molecular-beam data and ab initio calculations. Potential-energy surfaces used in previous work overestimate the binding of Ar to the SAM, leading to larger energy transfer than found in the experiments. New calculations, based on empirical force fields… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(11 citation statements)
references
References 43 publications
(60 reference statements)
1
10
0
Order By: Relevance
“…18,27,28 Briefly, we divide the global potential into three terms: The potential describing the organic monolayer ͑surface poten-tial͒, the potential describing the CO molecule ͑gas poten-tial͒, and the potential for the CO/SAM interactions ͑gas/ surface potential͒. The OPLS force field 40-42 is used for the surface potential, as this standard force field bears out the experimental structure of the SAMs, including a 30°tilt of the chains.…”
Section: A Potential-energy Surfacesmentioning
confidence: 99%
See 2 more Smart Citations
“…18,27,28 Briefly, we divide the global potential into three terms: The potential describing the organic monolayer ͑surface poten-tial͒, the potential describing the CO molecule ͑gas poten-tial͒, and the potential for the CO/SAM interactions ͑gas/ surface potential͒. The OPLS force field 40-42 is used for the surface potential, as this standard force field bears out the experimental structure of the SAMs, including a 30°tilt of the chains.…”
Section: A Potential-energy Surfacesmentioning
confidence: 99%
“…45 Regarding the gas/surface potential, earlier work demonstrated that popular force fields commonly fail to model accurately intermolecular interactions involving gases with SAMs. 27 Instead, analytic potentials must be derived from high-quality ab initio calculations. 46 Therefore, in this work we have derived analytic potential-energy surfaces for CO/ SAM interactions from ab initio data.…”
Section: A Potential-energy Surfacesmentioning
confidence: 99%
See 1 more Smart Citation
“…A critically important element in this broader exploratory effort has been rigorous theoretical investigation, based on obtaining reliable interaction potentials between a particular gas and liquid system, and then performing molecular dynamics (MD) simulations of the collisional events. Time after time, this ongoing comparison between experiment and theory has helped uncover the most important details for our understanding, where one technique compliments the other in elucidating key chemical and physical processes at the interface. ,, In an effort to harness this symbiotic power between experiment and theory, the focus of our current study follows from the work of many others in the chemical physics community, where we compare previous experimental studies of CO 2 + perfluorinated liquids (PFPE) with detailed theoretical MD simulations of CO 2 + fluorinated self-assembled monolayers (F-SAMs). In this comparison, we utilize results from theoretical trajectories to extract final scattering distributions and time-dependent surface structural metrics to help understand energy transfer dynamics at the gas−liquid interface, and in particular what might distinguish such dynamics from those at a gas–solid surface.…”
Section: Introductionmentioning
confidence: 99%
“…Along with these quantum state resolved experimental studies, classical molecular dynamics (MD) simulations of CO 2 + fluorinated self-assembled monolayers (F-SAMs) have been pursued, which provide considerable additional insight into the nature of the gas−liquid interaction. Prospects for meaningful comparison of quantum states formed from CO 2 + F-SAM versus CO 2 + liquid PFPE surfaces stem from a similarity in physical properties. For example, liquid perfluoropolyether (PFPE) and F-SAM surfaces have nearly identical density (1.87 vs 1.93 g/cm 3 , respectively), , thermal expansion (8.3 × 10 −4 vs 1.0 × 10 −3 K −1 ), , and surface tension (17 vs ≈ 15 dyn/cm). , Interestingly, both surfaces are characteristically rougher than single crystal metals, yet the root mean square (rms) surface deviations are nearly twice as large for PFPE (≈7 Å) compared to the F-SAMs (≈4 Å) under room temperature conditions.…”
Section: Introductionmentioning
confidence: 99%